FORMATIVE GRAMMAR ASSESSMENT IN BLENDED LEARNING ENVIRONMENTS: CHALLENGES AND SOLUTIONS - Hastin Yoka Ariyani; Masagus Firdaus; Santi Mayasari (Didascein : Journal of English Education, 2025)
Formative grammar assessment is crucial in English language learning, especially in building students' accuracy and awareness of language structure. In the modern era of education, blended learning approaches, which combine face-to-face and online learning, have become a popular strategy in increasing student flexibility and engagement. However, implementing formative grammar assessment in a blended learning environment faces several challenges, such as limitations of real-time feedback, difficulties in monitoring individual development consistently, and limitations of automated evaluation tools. The subjects in this study are students of the D3 Hospitality Study Program, who are in semesters II and IV, and are taking English courses emphasizing grammar. A total of 30 students were purposively. This study uses a qualitative case study approach to describe the practice of formative grammar assessment in blended learning. This article presents the results of a case study conducted at the Prasetiya Mandiri Polytechnic, involving D3 Hospitality students who took grammar courses in a blended system. Various assessments include interactive quizzes, weekly assignments, self-reflection, and online grammar discussions. The results show that integrating digital platforms such as Google Forms, Moodle, and learning analytics features can increase the effectiveness of formative assessments. In addition, micro-assessment and peer feedback strategies are practical solutions for overcoming the limitations of direct interaction. This article recommends adaptive approaches and the use of technology to strengthen the grammar assessment process in blended learning.